017 A network model of semantic dementia. Issue 3 (9th February 2012) - Fletcher, P; Warren, J D
Abstract : Semantic dementia (SD) is a unique syndrome in the frontotemporal lobar degeneration spectrum. Typically presenting as a progressive, fluent anomic aphasia, SD is the paradigmatic disorder of semantic memory with a characteristic anatomical profile of asymmetric, selective antero-inferior temporal lobe atrophy. Histopathologically, most cases show a specific pattern of abnormal deposition of protein TDP-43. This relatively close clinical, anatomical and pathological correspondence suggests SD as a promising target for future therapeutic trials. However, rational drug design and monitoring is likely to require a comprehensive understanding of how the molecular insult in SD translates to a clinico-anatomical phenotype. Here we propose a pathophysiological model of SD. The model is motivated by neuropsychological and neuroimaging data and posits the sequential, regionally determined disintegration of a vulnerable neural network. The key features of the model are: (1) existence of local zones of synaptic convergence within the temporal lobe with predictable network organisation; (2) a mechanism (or mechanisms) for transynaptic action of the molecular insult; and (3) establishment of a gradient of neuronal damage across the affected network, both within and between the temporal lobes. The model makes empirically testable predictions concerning the evolution of regional atrophy in SD.